Evaluation Of Acute Effect Of Ventricular Tachycardia Ablation On Qt Dispersıon, Tp-Te Interval And Tp-Te/Qt Ratio In Patients With Ischemic Dilated Cardiomyopathy - (:unkn) unknown (My University, 2020)
INTRODUCTION: There is limited data in the literatureregarding the effect of scar tissue on left ventricular (LV)repolarization process in patients with cardiomyopathy. Theaim of present study is to evaluate the acute effect ofventricular tachycardia (VT) ablation on dispersion of LVrepolarization which is suggested to play a role in initiatingand sustaining arrhythmia.METHODS: A total of 27 consecutive patients with ischemiccardiomyopathy who had undergone VT ablation constitutedour study population. Electrocardiographic recordingsobtained at the time of hospitalization and after the procedurewere retrospectively evaluated for the QTc dispersion, Tp-Teinterval and Tp-Te/QT ratio which are suggested to benoninvasive markers of dispersion of ventricularrepolarization. Significance of difference betweenelectrocardiographic parameters obtained before and after VTablation was evaluated.RESULTS: There was no significant difference between preand post ablation state regarding QTc dispersion (47.8 ± 28.3msec vs 42.4 ± 16.0 msec, p: 0.42), Tp-Te interval (derivationV5; 92.2 ± 26.6 msec vs 96.4 ± 24.9 msec, p: 0.40) and TpTe/QT ratio (derivation V5; 0.21 ± 0.06 vs 0.22 ± 0.06, p:0.43).DISCUSSION AND CONCLUSION: VT ablation did notalter electrocardiographic parameters that are assumed torepresent heterogeneity and transmural dispersion ofrepolarization in the immediate post procedure state.

GİRİŞ ve AMAÇ: Literatürde kardiyomiyopati hastalarında skar dokusunun sol ventrikül repolarizasyon süreci üzerine etkileri ile ilgili sınırlı veri bulunmaktadır. Mevcut çalışmada amaç ventrikül taşikardi (VT) ablasyonunun aritmi başlangıcı ve sürdürülmesinde rolü olduğu iddia edilen sol ventrikül repolarizasyon dispersiyonu üzerine akut etkisinin araştırılmasıdır. YÖNTEM ve GEREÇLER: İskemik kardiyomiyopatisi olan ve VT ablasyonu yapılan sıralı 27 hasta çalışma popülasyonumuzu oluşturdu. Hastaneye yatış esnasında ve işlemden sonra elde edilen elektrokardiyografik kayıtlar retrospektif olarak ventrikül repolarizasyon dispersiyonunun noninvaziv göstergeleri oldukları iddia edilen QTc dispersiyonu, Tp-Te intervali ve Tp-Te/QT oranı açısından değerlendirildi. VT ablasyonu öncesi ve sonrasında elde edilen parametreler arasındaki farkın önemi araştırıldı. BULGULAR: Ablasyon öncesi ve sonrası dönem arasında QTc dispersiyonu (47.8 ± 28.3 msn vs 42.4 ± 16.0 msn, p: 0.42), Tp-Te intervali (derivasyon V5; 92.2 ± 26.6 msn vs 96.4 ± 24.9 msn, p: 0.40) ve Tp-Te/QT oranı (derivasyon V5; 0.21 ± 0.06 vs 0.22 ± 0.06, p: 0.43) açısından önemli farklılık yoktu. TARTIŞMA ve SONUÇ: VT ablasyonu işlemin hemen sonrasında repolarizasyon heterojenitesini ve transmural dispersiyonunu yansıttığı iddia edilen elektrokardiyografik parametrelerde değişikliğe neden olmadı.
İskemik Dilate Kardiyomiyopati Hastalarında Ventriküler Taşikardi Ablasyonunun Qt Dispersiyonu, Tp-Te İntervali Ve Tp-Te/Qt Oranı Üzerine Akut Etkilerinin Araştırılması